2007
DOI: 10.1093/ije/dym065
|View full text |Cite
|
Sign up to set email alerts
|

House-level risk factors for triatomine infestation in Colombia

Abstract: Surveillance of a few easily assessed household characteristics provides an accurate, rapid assessment of house-level variation in risk. Measured effect sizes for specific structural characteristics could be used to maximize the cost-effectiveness of programmes to reduce vector infestation and interrupt Chagas disease transmission by improving house quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 26 publications
2
60
0
4
Order By: Relevance
“…These building materials have been previously identified as risk factors for Chagas disease in Colombia and other countries [34][35][36][37][38][39][40] and might explain the proportions of houses with presence of vectors found in these communities because the number of houses constructed with these materials is higher in Seminke, followed by Marocazo, and finally by Sabana de Joaquina.…”
Section: Discussionmentioning
confidence: 99%
“…These building materials have been previously identified as risk factors for Chagas disease in Colombia and other countries [34][35][36][37][38][39][40] and might explain the proportions of houses with presence of vectors found in these communities because the number of houses constructed with these materials is higher in Seminke, followed by Marocazo, and finally by Sabana de Joaquina.…”
Section: Discussionmentioning
confidence: 99%
“…Housing conditions have been investigated in Colombia as risk factors associated with the presence of triatomines inside households. 24 Although our study explored the association with a different but related outcome (T. cruzi infection), some variables, such as having animals inside the houses, could be related to infections in households.…”
Section: Discussionmentioning
confidence: 99%
“…8,[11][12][13][14][15][16][17] A study carried out in Colombia to evaluate the house-level risk factors for triatomine infestation showed that domestic infestation is associated with over seven inhabitants (odds ratio [OR] = 1.24, 95% confidence interval [95% CI] = 1.11-1.39), overhead storage space (OR = 1.16, 95% CI = 1.03-1.32), a grain shed (OR = 1.25, 95% CI = 1.02-1.52), and the presence of cats (OR = 1.27, 95% CI = 1.14-1.42). 18 In Colombia, T. dimidiata has a great capacity to adapt to different environments, including sylvatic ecotypes, such as caves, rocks, tree holes, palms, and vertebrates' nests, in wet and dry zones and over a wide altitudinal range. It tends to inhabit urban and periurban areas because of its attraction to lights.…”
Section: Introductionmentioning
confidence: 99%